Jointly experimenting for transformation? Shaping real-world laboratories by comparing them. - Schäpke, Niko; Stelzer, Franziska; Caniglia, Guido; Bergmann, Matthias; Wanner, Matthias; Singer-Brodowski, Mandy; Loorbach, Derk; Olsson, Per; Baedeker, Carolin; Lang, Daniel J. (Oekom, 2018)
Various experimental approaches of transformative research in real-world settings have emerged. Yet, similarities, differences, and specific contributions remain unclear. A characteristic-based comparison reveals complementarities and provides orientation. Real-world laboratories (RwLs, German Reallabore) belong to a family of increasingly popular experimental and transdisciplinary research approaches at the science-society interface. As these approaches in general, and RwLs in particular, often lack clear definitions of key characteristics and their operationalization, we make two contributions in this article. First, we identify five core characteristics of RwLs: contribution to transformation, experimental methods, transdisciplinary research mode, scalability and transferability of results, as well as scientific and societal learning and reflexivity. Second, we compare RwLs to similar research approaches according to the five characteristics. In this way, we provide an orientation on experimental and transdisciplinary research for societal transformations, and reveal the contributions of this type of research in supporting societal change. Our findings enable learning across the different approaches and highlight their complementarities, with a particular focus on RwLs.
Keywords: Nachhaltige Entwicklung; Nachhaltige Stadtentwicklung; Urban Governance; Wissenschaft; Forschungsmethode; Wissenstransfer; Reallabor; Projekt; Vergleichsuntersuchung; Internationaler Vergleich; Transdisziplinarität